Morality Management and Situation Ethics: Metatheory and Practice - Jan Franciszek Jacko (Routledge, 2025)
This book presents the philosophical assumptions of situation ethics to show the practice of morality management that follows from them. This research comprises theoretical and applied aspects: It is an investigation into metaethics that encompasses strategic and quality management problems. With the example of situation ethics, the book illustrates the role of philosophical investigations and solutions in management theory and practice. It will be of interest to researchers, academics and advanced students in the fields of business and management studies, ethics, quality management and philosophy. Furthermore, this book may be useful for senior executives and politicians charged with negotiating complicated moral quandaries and overseeing the implementation of ethical policies in their organisations and communities.
Keywords: 170; Morality; Management; Situation Ethics; Ethics; Metatheory; Practice; Morality Management